Dietary behavior and physical activity among pupils of sports and general class in Ustrzyki Dolne - Marcysiak, Małgorzata; Ciosek, Anna; Żywica, Małgorzata; Prządak, Emilia; Banasiewicz, Daniel; Marcysiak, Miłosz; Zagroba, Małgorzata; Ostrowska, Bożena; Skotnicka-Klonowicz, Grażyna (Nursing Problems / Problemy Pielęgniarstwa, 2009)
Introduction. Correct nutrition deals with optimum fulfilling the dietary needs. It fulfils the energy, vitamins, etc. nutrition which does not provide the above leads to malnutrition or development of civilization illnesses which include obesity. A very important factor in obesity prevention apart from good nutrition is the physical activity. The prophylactic activities must be taken and conducted among children and teenagers. In order to make the actions effective it is necessary to research and get to know the dietary behaviour and level of their physical activity. Aim. Getting to know the dietary behaviour of primary and junior secondary schools with general and sport profile with taking into consideration their physical activity. Material and methods. The research was conducted with a diagnostic survey method. The survey was written by ourselves. The research was conducted among 191 pupils of primary and junior secondary schools in Ustrzyki Dolne. The mediums and variances were counted. To compare the collected data the statistic t-student was used for independent variables. The level of importance of statistical conclusions was estimated at the level of p < 0,05. Results. 89 primary school and junior secondary pupils took part in the research (general profile), and 102 (sport profile class) aged 11–15, with 96 girls and 95 boys. The obese and obese-endangered were 30% of general classes and 20% of sport classes. The assessment of dietary behaviour in the researched group showed the average behaviour at 59%, low at 27% and unsatisfactory with 3% of the questioned. Only 2% represented a high level of healthy behaviour and 8% at the satisfactory level. The analysis of relations between the level of dietary behaviour and a place of residence, sex and profile of education/class did not show big differences. In the researched group most students preferred active forms of free time activities. However, 4% indicated they did not do any sport at all. Conclusions: 1. In the researched group of students the school’s profile did not affect the dietary behaviour and physical activity. 2. It is necessary to take up educational activities which will promote a healthy lifestyle in all schools no matter what profile they have.